Effect of acetone/methanol ratio as a hybrid solvent on fabrication of polymethylmethacrylate optical fiber sensor - Samavati, Z. (Elsevier Ltd, 2020)
The key success for fabrication of highly sensitive optical fiber probe is precise control of cladding thickness and surface roughness. An easy, economic and accurate chemical etching technique for fabrication of multimode polymer fibers sensor is investigated. The cladding diameter of multimode optical fiber is reduced up to ~100 nm by immersing in mixture of acetone/methanol. To obtain the required cladding diameter and roughness, the etching time, solvent concentration and etching temperature have been varied. An approach for dynamic monitoring of etching using 850 nm light power transmitted through the fiber is used to determine the optimum solvent concentration in which the sensitivity of the probe is highest. The fabricated sensors are subjected to detect the refractive index changes of saline and crude oil having different concentrations. The maximum sensitivities of ~9.1 and ~24.2 dB/RIU are achieved once the probe immersed in saline and crude oil respectively. The optimum parameters for having highly sensitive sensor are mixture of acetone/methanol in the rate of 40/60 and solvent temperature of 15 Â°C. Interference of core and cladding mode, scattering, refraction, and absorption of evanescent waves are responsible for light intensity modulation. Â© 2019 Elsevier Ltd